2018
DOI: 10.1002/jbm.b.34178
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response to 3‐D Printed Bioactive Silicate and Borosilicate Glass Scaffolds

Abstract: The repair and regeneration of loaded segmental bone defects is a challenge for both materials and biomedical science communities. Our recent work demonstrated the capability of bioactive glass in supporting bone healing and defect bridging using a rabbit femur segmental defect model without growth factors or bone marrow stromal cells (BMSCs). Here in the current work, a comprehensive in vitro evaluation of bioactive silicate (13-93) and borosilicate (2B6Sr) glass scaffolds was conducted to provide further und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Bioactive glass (BAG) is a unique material that was recently suggested for a variety of applications in medicine and dentistry (Jones 2013), including stimulating bone formation (Jia et al 2018), desensitizing teeth (Wang et al 2010; Mitchell et al 2011; Lopez et al 2017), remineralizing white spot lesions (Bakry et al 2018), and restoring teeth (Par et al 2018). BAG was also recently suggested as an additive to resin-based dental composites for the purpose of releasing metal ions and influencing the formation of oral biofilms (Xu et al 2015; Khvostenko et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive glass (BAG) is a unique material that was recently suggested for a variety of applications in medicine and dentistry (Jones 2013), including stimulating bone formation (Jia et al 2018), desensitizing teeth (Wang et al 2010; Mitchell et al 2011; Lopez et al 2017), remineralizing white spot lesions (Bakry et al 2018), and restoring teeth (Par et al 2018). BAG was also recently suggested as an additive to resin-based dental composites for the purpose of releasing metal ions and influencing the formation of oral biofilms (Xu et al 2015; Khvostenko et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the synthetic and natural polymers, bioactive glasses (BGs) have also been used in vascular 3D bioprinting, because some BGs have the properties to enhance angiogenesis [153][154][155][156]. Early in 2005, Day et al showed that the conditioned medium, collected from fibroblasts and seeded with alginate beads containing 0.1 wt.% 45S5 glass particles, could increase endothelial cell proliferation rate and tubule formation phenomenon [157].…”
Section: Biomaterialsmentioning
confidence: 99%
“…Human fibroblasts, coated with 45S5 glass particles (<5 µm), could secrete large amounts of VEGFs and basic fibroblast growth factors (bFGFs). In 2019, Jia et al used extrusion-printed bioactive silicate and borosilicate (2B6Sr) glass scaffolds to culture MC3T3-E1 mouse pre-osteoblasts in vitro [155]. The results demonstrated that both the scaffolds were supported by VEGF assay with the capabilities for improving cells to attach, and promoting angiogenesis.…”
Section: Biomaterialsmentioning
confidence: 99%
“…The ability of bioactive glass to promote angiogenesis was further confirmed in an in vitro study by measuring elevated VEGF levels in a MC3T3-E1 line of murine preosteoblastic cells seeded on glass scaffolds. 121 In a recent study, Wu et al 122 developed an injectable hydrogel with copper-containing bioactive glass nanoparticles. The resulting gel triggered the growth of seeded MC3T3-E1 cells and human umbilical vein endothelial cells, and fully restored bone defects with the formation of vascularized bone tissue in a critical-size rat calvarial bone defect model.…”
Section: Scaffold-based Vascularization Strategiesmentioning
confidence: 99%